The Important Role of Evaluation of Indonesian Language Learning on Language Skills in Class X High School - Sanita; Ghufroni; Nur Faojiyah; Pandu Prassetio (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to find out the development of Indonesian language learning, especially in language skills. Another purpose of holding learning evaluations is so that teachers can find out the extent of students' abilities in learning, and can improve learning so that later students can improve more in learning. Evaluation of learning in schools, especially in SMA, SMK, and SMU, is considered important for improving students' learning abilities, especially in class X SMA, evaluation of the progress of student achievement needs to be observed as a whole because at this time after graduating from Junior High School (SMP), students go on to high school (SMA), will the abilities of the students still follow them when they are still in junior high school or have they started to develop when they go to high school. In this research method the author uses a quantitative descriptive method by collecting various data, objects and observations around which are put together. The results of the important role of evaluating Indonesian language learning in language skills in class X, are reflected in the 4 Indonesian language skills, namely: listening skills, writing skills, reading skills, speaking skills.